Analisis Peran Guru Sejarah dalam Menanamkan Nilai-nilai Kearifan Lokal Kepada Siswa di Sekolah Madrasah Aliyah Tahfizhil Qur’an Melalui Mata Pelajaran Sejarah - Lestari, Indah; Nababan, Surya Aymanda; Rahmat, Doris; Sumantri, Pulung; Darma, Aditya (Medan Resource Center, 2023)
Indonesia is a diverse country. This diversity presents great potential, especially in terms of cultural diversity and local wisdom values that reflect the socio-cultural aspects of Indonesian society. It is important to continue, teach, develop, and preserve this distinctive character amidst globalization, particularly to the younger generation. One way to do this is by integrating education that instills local wisdom values into the teaching and learning activities of Indonesian History and History subjects. Integrating education that instills local wisdom values into the teaching and learning activities of Indonesian History and History subjects is essential because it serves as a means for students to understand and appreciate their own culture. Local wisdom is an integral part of a society's culture and cannot be separated from the language of that community. Local wisdom is usually passed down from one generation to another through oral traditions, such as folk tales, proverbs, songs, and traditional games. Local wisdom is a knowledge that is discovered by a particular local community through a collection of experiences while adapting and integrating with their understanding of culture and the natural environment of a place. One way to instill local wisdom values is through the use of teaching methods, instructional materials, and learning media in Indonesian History lessons.